Signification, Objectification, and the Mimetic Uncanny in Claude Debussy’s “Golliwog’s Cakewalk” - de Martelly, Elizabeth (Current Musicology, 2010)
On October 30, 1905, Emma Bardac gave birth to Claude Debussy’s only child, a daughter named Claude-Emma (1905-1919). Debussy was a doting father; he dedicated his 1908 piano suite entitled “Children’s Corner” to her, and named four of the six movement after her toys. One of them is called “Golliwogs Cakewalk”, after a popular minstrel doll. Several elements about this suite problematizes the childlike innocence portrayed in “Children’s Corner”. This movement has attracted much critical attention mainly for its juxtaposition of a ragtime inflected cakewalk with parodied quotations of Richard Wagner’s “Prelude” to Tristan and Isolde. Also, the term “cakewalk” describes a dance form that came to characterize a specific musical genre in mid-nineteenth century United States. Dance historian and musicologist Davinia Caddy’s exploration of the cakewalk traces the history of the dance from its roots in African-American slavery, to popular American entertainment, and finally to its arrival on the French soil as a white, bourgeois leisure activity.